REDESAIN PASAR BUHA KOTA MANADO DENGAN PENDEKATAN SUSTAINABLE ARCHITECTURE - Rumteh, cheril; Warouw, Felly Ferol; Attaufiq, Muhammad Muhdi (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2024)
The market is a place for sellers and buyers. This is due to the transaction process of goods/services and the bargaining that occurs. The characteristics of the market usually consist of stalls / stalls, and open lots available to traders. The appearance or overall feel of a shopping center that can make the market stand out among its competitors such as the facilities and infrastructure provided. In general, it is an area used for selling places that traders use as a means or facility in placing goods from services for sale. This is due to Pasar Buha which is a "traditional" type of market that has a place where cleanliness is not guaranteed because the mass layout of buildings in the area tends to be ineffective and the lack of facilities provided. Therefore, Buha Market is an appropriate object for redesign purposes.This activity is carried out to obtain data related to the needs and problems in the design process. The data includes field surveys on related sites as well as interviews with several visitors or existing communities and related government parties. The data collected includes physical site data and documentation in the form of photos, videos, or sketches. Physical site data in the form of: Site potential and shortcomings, site boundaries, site topography and site size, view, site circulation, existing vegetation, and climate.Redesign of Manado City Buha Market with Sustainable Architecture Approach concludes that this redesign will be a means for people to shop at the Market with facilities that have supported the activities and needs of the people who come to shop and are equipped with sustainable architecture including: 1) Using natural and reusable materials, 2) Applying solar panels to reduce the use of conventional electricity, 3) Using secondary skin on building walls from natural materials, namely plants and natural stones. The redesign aims to provide comfort and better market quality for humans and the environment.